Reconstruction of Islamic Education Philosophy in the Digital Era: Integration of Revelation Values, Rationality, and Technological Literacy - Hamidah Alimuddin; Alim Bakhri; Abdul Halik (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The development of the digital era has brought significant changes to the education system, including Islamic education. However, these changes have not yet been fully accompanied by a philosophical reconstruction capable of addressing the challenges of technological advancement and the value crisis that arise within the digital society. This research aims to reconstruct the philosophy of Islamic education thru the integration of revelation values, rationality, and technological literacy as an epistemological foundation in facing the digital era. This research uses a qualitative method with a library research approach. Data were obtained thru a study of various literatures, such as books, scientific journals, articles, and other relevant sources related to Islamic educational philosophy and digital education transformation. Data analysis was conducted descriptively-analytically with a philosophical approach. The research results indicate that the reconstruction of Islamic education philosophy needs to be directed toward the integration of transcendental values, critical thinking skills, and balanced mastery of digital technology. Islamic education is not only oriented toward the transfer of knowledge but also toward character formation, digital ethics, and the spiritual awareness of students. Thus, the philosophy of Islamic education in the digital era can become a paradigm of education that is adaptive, humanistic, and remains grounded in Islamic values.